Buku Ajar Keperawatan Medikal Bedah : Gangguan Respirasi, Gangguan Muskuloskeletal / Vol. 4 Edisi 5 - LEMONE, Priscilla (EGC, 2015)
Buku Ajar Keperawatan Medikal Bedah : Gangguan Respirasi, Gangguan Muskuloskeletal / Vol. 4 Edisi 5